MEMBANGUN KESETARAAN GENDER DALAM KELUARGA PASANGAN PEKERJA - Panji Nurrahman (Jurnal Harkat : Media Komunikasi Gender, 2022)
Abstract. This study aims to explain how gender inequality occurs in the families of working spouses and to explain the actual roles of men and women in the family based on Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law. This research is a type of field research. Data collection is done by interviewing and searching written sources such as books and journals that are related to the object of this research. While the data analysis was carried out with qualitative data analysis techniques. The results of this study found several points. First, the gender inequality that occurs is caused by the culture that is constructed in society. Second, gender injustice in family life still occurs and the forms of gender injustice include marginalization, subordination, stereotypes, violence and double burden. Third, the two pairs of workers who became informants in this study in their family lives experienced gender injustice, namely double barden, but even so their families were still happy because their main role in the family was carried out with full responsibility. Gender equality in the families of working couples must be realized through strengthening the fair division of roles between men and women in the family in accordance with Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law. Abstrak. Penelitian ini bertujuan untuk menjelaskan bagaimana ketidakadilan gender terjadi dalam keluarga pasangan pekerja dan menjelaskan bagaimana sebenarnya peran dari laki-laki dan perempuan dalam keluarga berdasarkan Undang-undang Nomor 1 tahun 1974 tentang perkawinan dan Kompilasi Hukum Islam. Penelitian ini merupakan jenis penelitian lapangan. Pengumpulan data dilakukan dengan wawancara dan penelusuran sumber-sumber tertulis seperti buku dan jurnal yang memiliki keterkaitan dengan objek penelitian ini. Sedangkan analisis data dilakukan dengan teknik analisis data kualitatif. Hasil dari penelitian ini menemukan beberapa poin. Pertama, ketidakadilan gender yang terjadi disebabkan karena budaya yang terkonstruksi di masyarakat. Kedua, ketidakadilan gender dalam kehidupan keluarga masih banyak terjadi dan bentuk-bentuk ketidakadilan gender tersebut di antaranya, marginalisasi, subordinasi, stereotype, violence dan double burden. Ketiga, dua pasangan pekerja yang menjadi informan dalam penelitian ini dalam kehidupan keluarganya mengalami ketidakadilan gender yaitu double barden, tetapi meskipun demikian keluarganya tetap bahagia karena peran utama mereka dalam keluarga dilaksanakan dengan penuh tanggung jawab. Kesetaraan gender dalam keluarga pasangan pekerja wajib diwujudkan melalui penguatan pembagian peran yang adil antara laki-laki dan perempuan dalam keluarga yang sesuai dengan Undang-undang Nomor 1 tahun 1974 tentang perkawinan dan Kompilasi Hukum Islam.